2021
DOI: 10.3390/d13100469
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Algicidal Bacillus mycoides on Diatom Ulnaria acus from Lake Baikal

Abstract: Algae–bacteria interactions play an important role in water ecosystems. In this work, the BS2-15 algicidal strain was isolated from the bottom sediments of Lake Baikal and identified as Bacillus mycoides on the basis of 16S rDNA sequencing, its described ultrastructure, and biochemical properties. B. mycoides BS2-15 was demonstrated to have a strong algicidal effect against a freshwater diatom culture of Ulnaria acus, inhibiting its growth and increasing frustules fragility. By analyzing the impact of bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Our work studied the changes in the expression of these genes during active cell proliferation and when division stopped during prolonged culturing. We also tracked the effect of a silica shortage and an algicidal strain of B. mycoides previously shown to kill U. acus cultures [68].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our work studied the changes in the expression of these genes during active cell proliferation and when division stopped during prolonged culturing. We also tracked the effect of a silica shortage and an algicidal strain of B. mycoides previously shown to kill U. acus cultures [68].…”
Section: Discussionmentioning
confidence: 99%
“…To study the MC, DSP, ALDH, and GSHS involvement in the physiological adaptation of U. acus to stresses, we cultured cells under Si starvation as a key division-limiting factor, in conditions of a prolonged culture where cells are known to stop division as a result of depletion in nutrients [86], and under exposure to an algicidal bacterial filtrate. We had previously demonstrated that U. acus cells stopped dividing during the first three days and perished rapidly during the next seven days after the addition of the Bacillus mycoides bacterial filtrate [68]. We suggested that the bacteria-produced algicidal agent activated mechanisms against stress.…”
Section: Changes In MC Aldh12 Gshs and Dsp Expressionmentioning
confidence: 96%
See 1 more Smart Citation
“…algicidal bacteria leads to vacuolization, degradation of organelles, destruction of chloroplasts and mitochondria, and destruction of the cell shell. Study of the effect of Bacillus mycoides on Ulnaria acus found the destruction of the cell shell, DNA fragmentation, the accumulation of neutral lipids in diatom cells, the destruction of the nuclear membrane, but intact chloroplasts and mitochondria (Bedoshvili et al, 2021). Diatoms, in turn, are also able to produce antibacterial substances.…”
Section: Effects Of Bacteria On Diatomsmentioning
confidence: 99%
“…Bacillus sp. has also been shown to have high algicidal activity against some species of HAB organisms, including cyanobacteria, dinoflagellates, and diatoms [ 16 , 23 , 24 ]. Therefore, to quickly obtain green and efficient algicidal bacteria, this paper attempts to screen an algicidal bacterium against A. pacificum from different commercial Bacillus strains.…”
Section: Introductionmentioning
confidence: 99%